Malaria control among Myanmar migrants in Thailand: a qualitative study of healthcare providers - Nichakan Inthitanon; Piyarat Sripoorote; Yupaporn Wattanagoon; Pattamaporn Petchvijit; Ammarind Anantjitsupha; Kyawt Mon Win; Nattawan Rachaphaew; Khaing Zin Zin Htwe; Kritsana Suk-aum; Peeriya Watakulsin; Liwang Cui; Jetsumon Sattabongkot; et al. (Malaria Journal)
Abstract Background Thailand has experienced a recent surge in malaria cases, particularly along the Thailand-Myanmar border, likely driven by the importation of infections by Myanmar migrants. Implementing malaria control measures, especially surveillance among these high-risk populations, presents significant challenges. This study aimed to identify key obstacles and propose targeted solutions for enhancing malaria control among Myanmar migrants in border areas of Thailand. Methods A cross-sectional qualitative study was conducted in early 2024. Semi-structured interviews were held with 20 government healthcare providers and village health volunteers involved in malaria control across three districts in western Thailand with the highest malaria caseloads. Data were analysed using thematic analysis. Results Respondents consistently linked the rise in malaria cases to increased cross-border migration from Myanmar following recent political unrest. Key challenges included difficulty locating and following up with short-term or undocumented migrants, language barriers that hinder health education, and delays in diagnosis because of limited infrastructure and reliance on rapid diagnostic tests in areas without electricity. Suggested solutions included deploying mobile malaria posts near informal border crossings, mandating malaria testing before worksite entry, and engaging local employers and community leaders to register new arrivals and support treatment adherence among migrants. Conclusions Ongoing political instability in Myanmar continues to drive a large and dynamic population of migrants into Thailand’s border regions, sustaining malaria importation and complicating elimination efforts. Tailored, migrant-responsive strategies, such as mobile surveillance near border crossings, community-based follow-up mechanisms, and infrastructure improvements, are urgently needed to close coverage gaps and achieve malaria elimination by 2030.